1996
DOI: 10.1111/j.1440-1746.1996.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of gastric histology after Helicobacter pylori eradication

Abstract: Helicobacter pylori causes chronic active gastritis and is thought to be associated with the development of gastric atrophy, intestinal metaplasia and carcinoma. As the effect of H. pylori eradication on this process is poorly understood, we sought to determine the long-term effects of H. pylori eradication on gastric histology. Fifty-four patients with duodenal ulceration associated with H. pylori infection received H. pylori eradication therapy in 1985/86 and either remained infected (n = 22) or had the infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 16 publications
4
67
1
1
Order By: Relevance
“…After 4 years, the antral mucosa does revert to nearly normal, although degenerate lymphoid aggregates may persist (38). Some investigators report that intestinal metaplasia remains unchanged (38,42,43), whereas others report a reduction in extent and severity (39,41).…”
Section: The Stomach After H Pylori Eradicationmentioning
confidence: 99%
“…After 4 years, the antral mucosa does revert to nearly normal, although degenerate lymphoid aggregates may persist (38). Some investigators report that intestinal metaplasia remains unchanged (38,42,43), whereas others report a reduction in extent and severity (39,41).…”
Section: The Stomach After H Pylori Eradicationmentioning
confidence: 99%
“…In the same way, other randomized studies identified that H. pylori eradication in intestinal metaplasia could be important in the regression of this precancerous lesion [76,[109][110][111]119,120]. Oppositely, other trials, both follow-up and randomized control, had not identified regression of intestinal metaplasia when H. pylori eradication was administrated [121][122][123][124][125][126][127][128][129].…”
Section: Discussionmentioning
confidence: 96%
“…There was no significant difference in gastric atrophy or in intestinal metaplasia between the two patient groups. 50 Annibale et al successfully eradicated H. pylori in 25 of 32 patients. After a year there was no improvement in gastric atrophy or intestinal metaplasia.…”
Section: Bacterial Factorsmentioning
confidence: 99%